Forecasting the demand of electrical energy in Hebron city - Haj, Yahya; ALowiwe, Yacoup (جامعة بوليتكنك فلسطين - طاقة, 2022)
Future development of electric power systems must pursue a number of different goals. The power system should be economically efficient, it should provide reliable energy supply and should not damage the environment. At the same time, operation and development of the system is influenced by a variety of uncertain and random factors. In this study, data and statistics of the electrical network load were collected from the Hebron distribution network within 5 years. The data and statistics will entered to the ETAP software. The network will be analyzed during peak periods, average loads, and summer time in order to obtain indicators of the network losses and economic feasibility to reduce them. All substation data was collected and then used to predict the load at each substation in 2050. The data of photovoltaic (PV) system will be collected to study the amount of the energy produced form the system, and then analyzed these data to estimate the power will be produced. Several scenarios will be developed to improve the network performance and efficiency such as adding a main station or build a ring system. Some of the substation was analyzed during peak periods, average loads, and summer time in order to obtain indicators of the network losses and economic feasibility to reduce them. In addition, several solutions were developed to solve the problems by adding main additional feeder to alduhdah substation to solve the problem of high load
CD, no of pages 93 , طاقة 3/2022
Keywords: electrical energy - Hebron